Quality Culture Innovation in Urban Islamic High Schools: Integration of Stakeholder Participation and Global Perspectives - Sai’in, Sai’in; Boeriswati, Endry; Karnati, Neti (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Islamic education in urban high schools faces unique challenges and opportunities amid global dynamics and local cultures. This journal aims to explore how innovation in quality culture within urban high schools can leverage cultural and global perspectives to enhance educational quality. Employing a literature review approach, this study integrates findings from various research related to multicultural education, service quality, and innovation in Islamic education. Through a comprehensive review of policies, practices, and educational models implemented in urban high schools, this study identifies key strategies for integrating local values with global demands. The research also analyzes the impact of cultural quality innovations on educational quality and stakeholder satisfaction, including students, parents, and educators. By reviewing current literature and relevant theories, this article provides deep insights into how urban high schools can adopt innovative approaches to improve educational quality while maintaining local cultural relevance in a global context.